University campus solid waste management : combining life cycle assessment and analytical hierarchy process /: combining life cycle assessment and analytical hierarchy process. (2017) - Ghazvinei, Pezhman Taherei; Mir, Masoud Aghajani; Darvishi, Hossein Hassanpour; Ariffin, Junaidah
No abstract available